2011
DOI: 10.4236/wjcmp.2011.14024
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Recombination Mechanisms of Large InAs/GaAs Quantum Dots

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In addition to that we see that the intensity of EL spectra decrease with increasing the applied electric field which may be attributed to the decrease in energy of the electron which proportional to the second power degree of the electric field [13] [16] [17]. Also we see that the quantum numbers (n c , l c , m c ) have a significant effects on photoluminescence peak energy at fixed value of applied electric field (e z ) which can be explained as Ref [10] where the authors concluded that to have more than one excitons by dots the probability must be considered, and must include other factors as relaxation time, radiative recombination rate, scattering, and others.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…In addition to that we see that the intensity of EL spectra decrease with increasing the applied electric field which may be attributed to the decrease in energy of the electron which proportional to the second power degree of the electric field [13] [16] [17]. Also we see that the quantum numbers (n c , l c , m c ) have a significant effects on photoluminescence peak energy at fixed value of applied electric field (e z ) which can be explained as Ref [10] where the authors concluded that to have more than one excitons by dots the probability must be considered, and must include other factors as relaxation time, radiative recombination rate, scattering, and others.…”
Section: Resultsmentioning
confidence: 64%
“…The authors of [10] studied the mechanisms of radiative recombination of large InAs/GaAs quantum dots, the large InAs/GaAs quantum dots optical properties were investigated by low-temperature photoluminescence versus excitation-power density. They concluded that to have more than one exciton by Journal of Applied Mathematics and Physics dots the probability must be considered, and we must revise the usual equation to correctly describe the origin of the recombination and must include other factors as relaxation time, radiative recombination rate, scattering, and others.…”
Section: Introductionmentioning
confidence: 99%
“…In this groups, they correspond to the condition where dominant carrier recombination mechanism is radiative (m ~ 1), mixture of radiative and nonradiative (associate with defects) (1 <m< 2), or nonradiative dominant (m ~ 2) (Hasbullah et al 2009). In other study, Martini et al (2011) reported that, in a double logarithmic scale, the integrated PL intensity increases linearly with the increasing excitation power density and can be described by the relation, 2where is the integrated PL intensity; and is the excitation power density (Jin et al 1997). The exponent α depends on the radiative recombination mechanisms and η is the coefficient related to the PL efficiency of the QDs and includes several effects as capture, absorption, ionization and recombination of excitons.…”
Section: Power Dependence Of Plmentioning
confidence: 99%
“…In this way, TL is one of a large family of luminescence phenomena [1,2]. The light emission from silicon quantum dots is an active research area because of its potential applications in the silicon-based optoelectronic devices [5][6][7][8]. The efficiency of the silicon light emitting devices can be increased with the help of various mechanisms.…”
Section: Introductionmentioning
confidence: 99%